Comparing the effects of medical cannabis for chronic pain patients with and without co-morbid anxiety: A cohort study. (4th March 2023) - Bapir, Lara; Erridge, Simon; Nicholas, Martha; Pillai, Manaswini; Dalavaye, Nishaanth; Holvey, Carl; Coomber, Ross; Hoare, Jonathan; Khan, Shaheen; Weatherall, Mark W; Rucker, James J; Platt, Michael; et al.
ABSTRACT: Introduction: There is growing evidence on the efficacy of cannabis-based medicinal products (CBMPs) for chronic pain (CP). Due to the interaction between CP and anxiety, and the potential impact of CBMPs on both anxiety and CP, this article aimed to compare the outcomes of CP patients with and without co-morbid anxiety following CBMP treatment. Methods: Participants were prospectively enrolled and categorized by baseline General Anxiety Disorder-7(GAD-7) scores, into 'no anxiety'(GAD-7 < 5) and 'anxiety'(GAD-7 ≥ 5) cohorts. Primary outcomes were changes in Brief Pain Inventory Short-Form, Short-form McGill Pain Questionnaire-2, Pain Visual Analogue Scale, Sleep Quality Scale (SQS), GAD-7 and EQ-5D-5L index values at 1, 3 and 6 months. Results: 1254 patients (anxiety = 711; no anxiety = 543) met inclusion criteria. Significant improvements in all primary outcomes were observed at all timepoints (p < 0.050), except GAD-7 in the no anxiety group(p > 0.050). The anxiety cohort reported greater improvements in EQ-5D-5L index values, SQS and GAD-7(p < 0.050), but there were no consistent differences in pain outcomes. Conclusion: A potential association between CBMPs and improvements in pain and health-related quality of life (HRQoL) in CP patients was identified. Those with co-morbid anxiety reported greater improvements in HRQoL.